2020
DOI: 10.1007/s40279-020-01359-9
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fixture Congestion on Performance During Professional Male Soccer Match-Play: A Systematic Critical Review with Meta-Analysis

Abstract: Background Fixture congestion (defined as a minimum of two successive bouts of match-play, with an inter-match recovery period of < 96 h) is a frequent and contemporary issue in professional soccer due to increased commercialisation of the sport and a rise in the number of domestic and international cup competitions. To date, there is no published systematic review or meta-analysis on the impact of fixture congestion on performance during soccer match play. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 56 publications
3
53
0
Order By: Relevance
“…Our study also shows that there is no difference in total distance between players due to playing in a single-or multi-match week, which is similar to other previous research [32], and postgame CK levels were similar to those reported by Bok and Jukic (2020) in Croatian national-team players. In both studies, post-game CK levels were determined in the morning of the first day after the match, less than 24 h post-match.…”
Section: Discussionsupporting
confidence: 92%
“…Our study also shows that there is no difference in total distance between players due to playing in a single-or multi-match week, which is similar to other previous research [32], and postgame CK levels were similar to those reported by Bok and Jukic (2020) in Croatian national-team players. In both studies, post-game CK levels were determined in the morning of the first day after the match, less than 24 h post-match.…”
Section: Discussionsupporting
confidence: 92%
“…This is possible given the requirements of the latter to be more involved in active training/matches during that moment of the season and given the likely need to rotate players. In fact, congested fixture periods are linked to the possibility of inducing greater TS [ 8 ], whilst they can impair physical match performance [ 23 , 24 , 25 ] and raise injury risk [ 22 , 26 ]. However, the values for ACWR were all below 1.3, independent of player status (see Table 2 ), which, in theory, may not represent exacerbated injury likelihood [ 27 ], despite the fact that such a question lacks consensus to date (see, for example, Impellizzeri et al [ 28 ]).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, during preseason, adaptation to training is key, with cold water treatments perhaps blunting the adaptive responses. 25 However, amid fixture-dense schedules, priority should be performance recovery (as opposed to concerns regarding adaptations) for the subsequent match 3 , with cold water techniques having some efficacy in these regards. 24 Therefore, the lack of compatibility between perceived effectiveness and use of a strategy, both in the current and previous studies 1, 14, 15, 18 , is likely reflective of the equivocal evidence base and lack of explicit evidence-led recommendations endorsing the strategy for accelerating recovery and performance enhancement.…”
Section: ***Insert Table 4***mentioning
confidence: 99%
“…Recovery strategies are imperative in team sports 1 and elite soccer 2 , where players can compete in ≥60 competitive matches per season with fixture congestion and limited recovery time between matches (2-4 days). 3 Insufficient recovery can impede match performance 2 , negatively affect player health 4 and increase overuse injury-risk. 2 Indeed, teams with lower injury rates within season are more successful in domestic leagues and cup competitions.…”
Section: Introductionmentioning
confidence: 99%